Public Finances Solvency in the Euro Area: True or False? - António Afonso; José Carlos Coelho (Center for Economic Studies and ifo Institute (CESifo), 2022)
We assess public finances solvency for Euro Area countries using quarterly data between 1999Q1 and 2020Q4. Through a country-by-country analysis, the answer to the title question is true. For most countries, (i) the primary budget balance reacts positively to the lagged public debt ratio and past primary government balances contribute to the reduction of the public debt ratio, indicating a Ricardian fiscal regime. Furthermore, in a panel framework: (ii) the response of revenues to government expenditures is higher from 2010 onwards, and, for higher average public debt ratios, the response is lower, while (iii) the response of the primary government balance to the lagged public debt ratio is lower from 2010 onwards and is higher for higher average public debt ratios; (iv) past primary budget balances allow the public debt ratio to be reduced, especially before 2010 and in countries whose average public debt ratio is between 60 and 90% of GDP. Using a rolling window method, we find that (v) fiscal sustainability coefficients are higher the higher the lagged public debt ratios, fiscal rule indexes and sovereign ratings. Conversely, after 2010 and in periods of legislative elections, those coefficients are lower.
Keywords: C23; H61; H63; E62; 330; fiscal sustainability; primary budget balance; public debt; panel data; rolling windows; Euro Area; quarterly fiscal data